Lead wire, grid and composite energy storage battery

By adopting a design using multi-strand glass fiber rope and tin alloy coated lead wire, combined with optimization of the injection molding frame and core assembly, the problems of low lead wire strength and poor shear resistance were solved, achieving uniform current transmission and improved battery performance.

CN120867091APending Publication Date: 2025-10-31CHAOWEI POWER GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410535798.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing lead wires in busbar grids have problems such as low strength, easy peeling, and poor shear resistance, resulting in low and uneven current conduction efficiency, which affects the performance and life of the battery.

Method used

The system employs multi-strand glass fiber ropes with a glass fiber core layer and a tin alloy coating layer arranged from the inside out. Combined with the injection molding frame design, the lead wires are distributed in multiple layers. The frequency of wire breakage is reduced by optimizing the alloy tapered channel of the mold core assembly, and the use of a diamond-shaped frame and cross ribs improves stability and current transmission efficiency.

Benefits of technology

It significantly improves the tensile strength and shear resistance of lead wire, ensures uniform current distribution in the active material region, increases battery utilization and cycle life, and reduces the frequency of wire breakage and material usage during production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120867091A_ABST
    Figure CN120867091A_ABST
Patent Text Reader

Abstract

The invention relates to a lead wire, a grid and a composite energy storage battery, and belongs to the technical field of lead-acid energy storage batteries, the lead wire comprises a glass fiber core layer and a tin alloy coating layer which are arranged from inside to outside, the glass fiber core layer is a glass fiber rope formed by twisting multiple strands of glass fibers, and the twist degree of the glass fiber rope is 70-120 twists / m. According to the lead wire, the glass fiber rope formed by twisting the multiple strands of glass fibers is adopted, so that the tensile strength and the overall shear strength of the glass fiber core layer and the tin alloy coating layer are remarkably improved compared with those of a single-strand-structure glass fiber rope when the lead wire is stretched and stressed in the length direction; the problems that a lead wire in the prior art is low in strength, easy to strip and poor in anti-shearing capacity are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lead-acid energy storage battery technology, and more particularly to a lead wire, grid, and composite energy storage battery. Background Technology

[0002] Energy storage batteries mainly refer to batteries used in solar power generation equipment, wind power generation equipment, and renewable energy storage. They have the advantages of high energy density, good safety performance, long cycle life, fast charging and discharging capability, low self-discharge rate, and green environmental protection.

[0003] The plates of a storage battery consist of a busbar grid and active material coated within the grid frame. The composite lead wires within the active material coating area act as current collectors for the plates, conducting current after activating the battery's performance. However, the lead wires in existing busbar grids cannot efficiently transfer current to the active material area and suffer from low strength, easy peeling, and poor shear resistance. Summary of the Invention

[0004] Based on the above analysis, the present invention aims to provide an injection-molded frame for a busbar grid, a busbar grid, an electrode plate, and a composite energy storage battery to solve at least one of the problems of low strength, easy peeling, and poor shear resistance of existing lead wires.

[0005] A lead wire includes: a glass fiber core layer and a tin alloy coating layer arranged from the inside out, wherein the glass fiber core layer is a glass fiber rope made of multiple strands of glass fiber twisted together.

[0006] Preferably, the twist of the glass fiber rope is 70 twists / m to 120 twists / m.

[0007] Preferably, the twist of the glass fiber rope is 90±9 twists / m.

[0008] Preferably, the number of glass fiber strands in the glass fiber rope is 3-5; the diameter of the glass fiber rope is 0.2mm-0.8mm.

[0009] Preferably, the glass fiber has a diameter of 0.23mm-0.8mm.

[0010] Preferably, the tin alloy coating is a lead-tin alloy with a tin content of 0.3%-1.3% by mass.

[0011] Preferably, the tin alloy coating of the lead wire for the positive electrode is a lead-tin alloy with a tin mass content of 1.0%-1.3%.

[0012] A busbar grid includes the aforementioned lead wire.

[0013] An electrode plate comprising the aforementioned busbar grid.

[0014] A composite energy storage battery includes a positive electrode busbar, a negative electrode busbar, multiple battery cells, and multiple electrode plates as described above;

[0015] The electrode plates and battery cells are stacked alternately.

[0016] The battery cell has two sides with opposite polarities;

[0017] Adjacent battery cells with the same electrode polarity are arranged facing each other and connected by electrode plates;

[0018] The electrode plates include a positive electrode plate and a negative electrode plate;

[0019] The end of the positive electrode plate is connected to the positive electrode busbar via a connector;

[0020] The end of the negative electrode plate is connected to the negative electrode busbar via a busbar connector;

[0021] The positive and negative busbars include conductive terminals, screw connections, and busbar grids;

[0022] The current-collecting grid includes multiple conductive ribs; each conductive rib is connected to multiple current-collecting connectors, and the current is collected in the conductive ribs through the current-collecting connectors.

[0023] Multiple busbars are distributed along the height of the conductive ribs, and each busbar can collect current from the electrode plate independently.

[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0025] 1. The lead wire of the present invention is made of glass fiber rope made of multiple strands of glass fiber, which significantly improves the tensile strength and overall shear strength of the glass fiber core layer and tin alloy coating layer when subjected to tensile stress in the length direction compared with single-strand glass fiber rope.

[0026] 2. In the injection-molded frame for the busbar grid of the present invention, the lead wire holes on the first frame are arranged in a single layer, and the lead wire holes on the second frame are arranged in at least two layers. This allows the lead wires to be distributed in at least two layers within the frame, forming a three-dimensional grid. The multi-layered distribution of lead wires is beneficial for the current transmission during battery use, and can ensure that the current density of each part of the plate is evenly distributed during charging and discharging, efficiently applying the current to the active material area, and achieving an active material utilization rate of 37-39%.

[0027] 3. The injection-molded frame for the busbar grid of the present invention can make the lead wires in a single grid distributed in multiple layers, which is equivalent to the multi-layer superposition of traditional single-layer lead wire grids. However, the total number of lead wires in the present invention does not change, so the weight of the grid changes very little.

[0028] 4. The injection-molded frame for the busbar grid of the present invention allows the lead wires in a single grid to be distributed in multiple layers. During the injection molding of the grid, the composite lead wires are placed in the mold, and there is a 10-second pause when the injection mold is closed. The injection direction of the injection molding compound is the direction marked by the curve in Figure 5. The side of the double-layer composite lead wires in the grid of the present invention that is opposite to the injection direction can be covered in reverse by the injection pressure, so that the entire grid can be covered with less overcoating when applying the active material, thereby increasing the conductive area of ​​the lead wires. The so-called overcoating refers to the thickness of the active material covering the current collector being 0.5mm to 0.8mm, and it is necessary to cover all the internal ribs of the injection-molded grid at this thickness.

[0029] 5. In the injection-molded frame for the busbar grid of the present invention, the cross-section of the first frame is trapezoidal, which can effectively protect the composite lead wire without active material coating from corrosion during the cycle life. Moreover, the four frames form a square frame for the electrode plate, which can suppress the expansion and shedding of active material during the cycle life.

[0030] 6. The cross-sections of the second, third, and fourth borders and the horizontal ribs of the present invention are all rhomboid, which can achieve the maximum stable support with the minimum injection molding material; moreover, the rhomboid structure occupies less volume and has less impact on the space occupied by the active material; in addition, the rhomboid structure makes demolding in the injection molding process easier.

[0031] 7. This invention adjusts the length of the conductive ribs based on the position of each conductive rib relative to the current-carrying area, optimizes the current transmission path of the conductive ribs in the current-carrying area, reduces the internal resistance of the battery, increases the specific energy, and achieves cost reduction and efficiency improvement, making full use of limited resources and improving utilization rate.

[0032] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description

[0033] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0034] Figure 1 This is an overall view of the die core assembly for producing composite lead wire according to the present invention;

[0035] Figure 2 This is a discrete structure diagram of the core assembly for producing composite lead wire according to the present invention;

[0036] Figure 3 for Figure 1Section A1-A1;

[0037] Figure 4 for Figure 3 A magnified view of part C in the middle;

[0038] Figure 5a This is a schematic diagram of the structure of a busbar grid including the injection-molded frame and lead wire of the present invention.

[0039] Figure 5b This is a schematic diagram of the structure of a busbar grid including the injection-molded frame and lead wire of the present invention (this diagram only shows the multi-layer lead wire, and does not show the first frame of the trapezoidal section and the second, third, and fourth frames of the rhomboid section and the transverse ribs of the rhomboid section).

[0040] Figure 6 This is a side view of one side of the second frame of the injection-molded frame for the busbar grid of the present invention.

[0041] Figure 7 This is a side view of one side of the first frame of the injection-molded frame for the busbar grid of the present invention.

[0042] Figure 8 This is a side view of the third frame side of the injection-molded frame for the busbar grid of the present invention.

[0043] Figure 9 This is a schematic diagram of the injection direction of the injection molding compound.

[0044] Figure 10 This is a three-dimensional view of the busbar of the present invention.

[0045] Figure 11 This is the main view of the busbar of the present invention.

[0046] Figure 12 This is a top view of the busbar of the present invention.

[0047] Figure 13 This is a side view of the busbar of the present invention.

[0048] Figure 14 This is a top view of the screw connection portion of the present invention.

[0049] Figure 15 This is an isometric side view of the composite energy storage battery of the present invention.

[0050] Figure 16 This is a side view of the composite energy storage battery of the present invention.

[0051] Figure 17 for Figure 12 Sectional view of plane AA.

[0052] Figure 18This is a diagram showing the variation of the height H of the center line of the longitudinal axis of the conductive rib with the position of the conductive rib relative to the axis of symmetry of the busbar in one embodiment of the present invention.

[0053] Figure 19a This is a graph showing the data from the cyclic test in Example 3.

[0054] Figure 19b The graph shows the data from the cyclic test in Comparative Example 4.

[0055] Figure label:

[0056] 101-Inlet mold; 10101-Core material inlet mold core; 10102-Inlet mold base; 10103-Core material inlet channel; 102-Intermediate mold; 10201-Alloy inlet; 103-Outlet mold; 10301-Core material lead-coated layer channel; 10302-Outlet mold core; 10303-Outlet mold base; 104-Alloy conical channel; l-Distance between the end face of the core material inlet mold core and the end of the conical inlet end of the core material lead-coated layer channel;

[0057] 1-First frame; 2-Second frame; 3-Third frame; 4-Fourth frame; 5-Lead wire hole; 6-Horizontal rib; 7-Lead wire; 8-Bus connector; 8a-First busbar connector; 8b-Second busbar connector; 9-Electric plate; 10-Positive busbar; 11-Negative busbar; 12-Battery unit;

[0058] 01-Conductive terminal block; 011-Column body; 012-Core body; 013-Screw hole; 02-Screw connection part; 021-Arc-shaped connection part; 03-Buffer grid; 031-Buffer area; 032-Conductive rib. Detailed Implementation

[0059] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0060] Terminology definition:

[0061] Twist refers to the number of turns per inch of yarn, which is the strength of a rope or yarn. It refers to the twisting of a fiber or yarn during spinning or weaving, and it affects the internal structure and mechanical properties of the fiber or yarn.

[0062] Reverse twist is a process used to make ropes from multi-strand forward twisted fibers.

[0063] On one hand, the present invention provides a lead wire comprising: a glass fiber core layer and a tin alloy coating layer arranged from the inside out, wherein the glass fiber core layer is a glass fiber rope made of multiple strands of glass fiber twisted together.

[0064] Compared with the prior art, the lead wire of the present invention is made of glass fiber rope made of multiple strands of glass fiber, which significantly improves the tensile strength and overall shear strength of the glass fiber core layer and tin alloy coating layer when subjected to tensile stress in the length direction compared with single-strand glass fiber rope.

[0065] Specifically, the glass fiber diameter is 0.23mm-0.8mm, and the glass fiber rope twist is 70-120 twists / m.

[0066] Specifically, the glass fiber rope has 3-5 strands of glass fiber and a diameter of 0.2mm-0.8mm.

[0067] It should be noted that the reason for choosing the above glass fiber diameter and twist is that when the above glass fiber diameter and twist are selected, the tensile strength and overall shear strength of the glass fiber core layer and tin alloy coating layer are both optimal when subjected to tensile stress in the length direction.

[0068] It should be noted that the process of making rope typically includes the following steps:

[0069] 1. Twisting: Twisting multiple strands of filament together with a certain twist and direction to form twisted yarn.

[0070] 2. Reverse twist: Rotating the twisted yarn in the opposite direction reduces the twist of the yarn and releases internal stress.

[0071] 3. Twisting: The reverse-twisted wires are twisted together according to a certain twist and direction to form the final glass fiber rope. Through these steps, the glass fiber filaments can be made more uniform and stable, improving their strength and toughness.

[0072] Reverse twisting of multi-strand glass fiber filaments refers to rotating multi-strand glass fiber filaments in the opposite direction to reduce the twist and internal stress of the filaments.

[0073] Preferably, the glass fiber diameter is 0.5 mm and the glass fiber rope twist is 90 ± 9 twists / m.

[0074] Specifically, the glass fiber basis weight is 0.110±0.011 g / m.

[0075] Specifically, the tin alloy cladding layer can be a lead-tin alloy with a tin mass content of 0.3%-1.3%.

[0076] Preferably, the tin alloy coating of the lead wire for the positive electrode is a lead-tin alloy with a tin mass content of 1.0%-1.3%.

[0077] Preferably, the tin alloy coating of the lead wire for the positive electrode is a lead-tin alloy with a tin mass content of 1.2%.

[0078] Preferably, the tin alloy coating of the lead wire for the negative electrode is a lead-tin alloy with a tin mass content of 0.3%-0.5%.

[0079] Preferably, the tin alloy coating of the lead wire for the negative electrode is a lead-tin alloy with a tin mass content of 0.3%.

[0080] It should be noted that the reason for the different tin content in the tin alloy coating of the lead wires used in the positive and negative electrodes is that the design of the lead wire alloy for the positive electrode grid needs to calculate the balance between oxidation rate and conductivity throughout the entire cycle life, while the negative electrode is reduced to spongy lead after the battery is activated, so oxidation and conductivity do not need to be considered, and only cost is considered to reduce the tin content.

[0081] Specifically, the thickness of the lead-tin alloy cladding layer is 0.25mm-1.0mm;

[0082] Preferably, the thickness of the lead-tin alloy coating layer of the lead wire for the positive electrode is 0.7mm-1.0mm; preferably, the thickness of the lead-tin alloy coating layer of the lead wire for the positive electrode is 0.75mm.

[0083] Preferably, the thickness of the lead-tin alloy coating layer of the lead wire used for the negative electrode is 0.25mm-0.6mm;

[0084] Preferably, the lead-tin alloy coating of the negative electrode lead wire has a thickness of 0.6 mm.

[0085] On the other hand, the present invention provides a method for forming lead wire, comprising: using a core assembly for producing composite lead wire, introducing molten alloy through an alloy inlet 10201, introducing core material through a core material guide core 10101, the alloy entering an alloy conical channel 104, and merging with the core material from the core material guide core 10101 before entering a core material coating lead layer channel 10301 for coating, thereby forming a composite lead wire; the alloy flow rate in the alloy conical channel 104 is 1.0-1.5 times that in the core material coating lead layer channel 10301, more preferably 1.0-1.2 times, and most preferably 1.1 times;

[0086] like Figures 1-4 As shown, the die core assembly for producing composite lead wire includes an inlet die 101, an intermediate die 102, and an outlet die 103. The inlet die 101 and the outlet die 103 are assembled and connected through the intermediate die 102. The intermediate die 102 is provided with an alloy inlet 10201.

[0087] The diameter of the inlet end of the lead-coated core material channel 10301 of the outlet mold 103 gradually decreases along the material flow direction, forming a conical inlet end;

[0088] The end of the core material inlet mold 10101 of the inlet mold 101 is tapered, and the tapered angle faces the outlet mold 103; the tapered end of the core material inlet mold 10101 is located inside the tapered inlet end of the outlet mold 103, and an alloy tapered channel 104 is formed between the two tapered shapes.

[0089] Compared with existing technologies, the composite lead wire forming method of the present invention employs a specific die core assembly for composite lead wire production. This die core assembly changes the traditional planar-to-planar junction of the inlet and outlet dies to a conical nested form, creating an alloy conical channel. Molten alloy from the intermediate die's alloy inlet and core material introduced into the die core from the inlet die converge within the alloy conical channel and are then coated. The alloy conical channel converts the alloy pressure into a thrust in the same direction as the composite core material's running track, effectively reducing the shear force exerted by the high pressure inside the furnace on the die core and composite core material. This prevents the high pressure of the alloy lead from directly acting on the composite core material, thereby reducing wire breakage failures, lowering the breakage frequency, and increasing production efficiency. The present invention limits the alloy flow rate in the alloy conical channel to the alloy flow rate in the core material coating lead layer channel, further reducing the breakage frequency and the diameter deviation of the composite lead wire.

[0090] It should be noted that, in this invention, the alloy refers to an alloy containing lead, i.e., lead alloy.

[0091] For example, the alloy flow rate in the alloy tapered channel 104 is 1.1 times the alloy flow rate in the core material coated lead layer channel 10301. A value that is too high will increase the breakage frequency, while a value that is too low will affect the quality of the composite lead wire.

[0092] For example, the alloy in the core material coated lead layer channel 10301 generates a thrust of 16MPa-22MPa in the direction of the core material coated lead layer channel 10301 outlet. For example, 17MPa, 18MPa, 19MPa, 20MPa, 21MPa.

[0093] For example, the temperature of the alloy is 190°C-215°C. For example, 195°C, 200°C, 205°C.

[0094] Specifically, for the positive electrode composite lead wire (wire size 2.0mm), the alloy temperature is 190-210℃; for the negative electrode composite lead wire (wire size 1.5mm), the alloy temperature is 195-215℃.

[0095] For example, the pressure of the alloy in the alloy inlet 10201 is 16MPa-22MPa. For example, 17MPa, 18MPa, 19MPa, 20MPa, 21MPa.

[0096] Understandably, the entire production process of composite lead wire involves the coordination of pressure, temperature, and flow rate. When the temperature remains constant, higher pressure will increase the flow rate. Under these conditions, changes in flow rate can lead to defective products such as off-center cores, broken cores, and large deviations in wire size. Similarly, when the pressure remains constant, higher temperature will also cause changes in flow rate. Under these conditions, defective products with uneven surfaces, burrs, or those that do not meet the testing standards (2.0 lead wire tensile strength ≥100N, 1.5 lead wire tensile strength ≥90N) may appear.

[0097] For example, the lead cladding speed is ≤80.0 m / min.

[0098] For example, the core material is a glass fiber core layer.

[0099] For example, the angle between the hypotenuse of the alloy tapered channel 104 and the horizontal line is greater than the angle between the hypotenuse of the tapered end of the core material guide mold core 10101 and the horizontal line.

[0100] In this invention, the function of the inlet mold 101 is to guide the core material into the core material coating lead layer channel 10301 of the outlet mold 103, ensuring that the core material and the outer alloy lead layer are concentric.

[0101] For example, the inlet mold 101 includes an inlet mold base 10102 and a core material inlet mold core 10101, wherein the core material inlet mold core 10101 is provided with a core material inlet channel 10103 for the core material to pass through.

[0102] In this invention, the exit mold 103 serves to guide the core material through the lead alloy layer before it is exported. The exit mold 103 includes an exit mold base 10303 and an exit mold core 10302; the exit mold 103 is provided with a core material lead coating channel 10301. The core material lead coating channel 10301 of this invention extends through both the inlet and outlet of the exit mold 103. That is, after the core material and alloy are combined, they travel a certain distance within the core material lead coating channel 10301 before the composite lead wire emerges. Compared to directly exiting the composite lead wire after the core material and alloy are combined, this improves the surface quality and uniformity of the coating layer.

[0103] In this invention, the intermediate mold 102 is used to fix the distance between the core material inlet channel 10103 of the inlet mold 101 and the core material lead coating layer channel 10301 of the outlet mold 103. The size of the distance determines the efficiency and quality of core material and alloy lead coating during the production of composite lead wire. Generally, when coating the alloy lead layer, the distance between the outlet mold core and the inlet mold core is large, and the production efficiency is very high. However, the core material is prone to breakage under large internal pressure during production. On the other hand, if the distance is small, the breakage is not easy, but the production efficiency is low. Therefore, adjusting the distance becomes the key factor in balancing production speed and core material failure.

[0104] Specifically, the intermediate mold 102 has an annular structure, and the inlet mold 101 and outlet mold 103 are respectively assembled at both ends of the intermediate mold 102. More specifically, the core material inlet mold core 10101 and the outlet mold core 10302 are respectively assembled within the annular sections at both ends of the intermediate mold 102. A cavity is provided between the intermediate mold 102 and the core material inlet mold core 10101. The alloy from the alloy inlet 10201 enters this cavity and then enters the alloy conical channel 104. The core material inlet channel 10103 is coaxially arranged with the core material lead-coated layer channel 10301.

[0105] For example, the angle between the hypotenuse of the alloy tapered channel 104 and the horizontal line is 10-35 degrees larger than the angle between the hypotenuse of the tapered end of the core material guide mold core 10101 and the horizontal line, for example, 12 degrees, 15 degrees, 17 degrees, 19 degrees, 20 degrees, 22 degrees, 24 degrees, 26 degrees, 28 degrees, 30 degrees, 32 degrees, or 34 degrees larger. Angle control can balance the lead input and output amounts while meeting the lead input requirements. However, excessively large or small angles will cause the raw material to deviate from balance, resulting in off-center composite lead wires or composite lead wires with surface burrs. In other words, off-center composite lead wires are where the core material is not centered in the cross-section. A wire diameter deviation greater than 0.3 mm is considered a defective product. This invention reduces the wire diameter deviation of composite lead wires by optimizing the cone angle of the alloy tapered channel 104.

[0106] Specifically, the included angle can be selected based on the diameter of the composite lead wire.

[0107] For example, when producing composite lead wire with a diameter of 1.5 mm, the angle between the hypotenuse of the tapered end of the core material guide die 10101 and the horizontal line is 30-35 degrees. For example, 31 degrees, 32 degrees, 33 degrees, or 34 degrees.

[0108] For example, when producing composite lead wire with a diameter of 1.5 mm, the angle between the hypotenuse of the alloy tapered channel 104 and the horizontal line is 45-65 degrees. For example, 46 degrees, 48 ​​degrees, 50 degrees, 52 degrees, 54 degrees, 56 degrees, 58 degrees, 60 degrees, 62 degrees, and 64 degrees.

[0109] For example, when producing composite lead wire with a diameter of 2.0 mm, the angle between the hypotenuse of the tapered end of the core material guide die 10101 and the horizontal line is 35-40 degrees. For example, 36 degrees, 37 degrees, 38 degrees, or 39 degrees.

[0110] For example, for producing composite lead wire with a diameter of 2.0 mm, the angle between the hypotenuse of the tapered end of the core material guide mold 10101 and the horizontal line is 60-75 degrees. For example, 62 degrees, 64 degrees, 68 degrees, 70 degrees, 72 degrees, and 74 degrees. For example, the distance l between the end face of the core material guide mold 10101 and the end of the tapered entrance of the core material coated lead layer channel 10301 is 1 / 2 to 3 / 5 of the diameter of the core material coated lead layer channel 10301, most preferably 1 / 2. This invention reduces the diameter deviation and breakage frequency of the composite lead wire by optimizing the distance l between the end face of the core material guide mold 10101 and the end of the tapered entrance of the core material coated lead layer channel 10301.

[0111] In other words, the distance l between the end face of the core material inlet mold 10101 and the end of the tapered entrance of the core material lead-coated channel 10301 is determined according to the diameter of the composite lead wire produced. For example, the distance l between the end face of the core material inlet mold 10101 and the end of the tapered entrance of the core material lead-coated channel 10301 is 0.8mm-1.2mm, such as 1.9mm, 1.0mm, or 1.1mm.

[0112] In this invention, the alloy and the core material converge in the alloy conical channel 104, which eliminates the phenomenon of core material breaking due to high pressure inside the mold. In order to further promote the flow of alloy into the alloy conical channel 104 and further reduce the shear force of system pressure on the core material guide mold core 10101, the projection of the inclined side of the conical end of the core material guide mold core 10101 on the horizontal plane is closer to the inlet end of the inlet mold 101 than the projection of the inclined side of the alloy conical channel 104 on the horizontal plane. That is, the inclined surface of the conical end of the core material guide mold core 10101 is offset from the inclined surface of the alloy conical channel 104, so that part of the inclined surface of the conical end of the core material guide mold core 10101 is not opposite to the inclined surface of the alloy conical channel 104. This part of the inclined surface plays a guiding role for the alloy, further reducing the shear force of system pressure on the core material guide mold core 10101.

[0113] Furthermore, the alloy inlet 10201 is directly opposite the inclined side of the tapered end of the core material guide mold 10101. In this embodiment, during the production of composite lead wire, the internal high pressure will directly act on the inclined surface of the core material guide mold 10101. The inclined surface changes the pressure direction to be consistent with the movement direction of the core material, further reducing the shearing force of the system pressure on the core material guide mold 10101, reducing wire breakage, and increasing work efficiency.

[0114] For example, the intermediate mold 102 is provided with two alloy inlets 10201.

[0115] For example, the two alloy inlets 10201 are symmetrical about the axis of the intermediate mold 102. This can promote pressure equalization of the introduced alloy.

[0116] Thirdly, the present invention provides a busbar grid, including the aforementioned lead wire 7, injection molded frame and active material, wherein the lead wire 7 passes through a set of opposite frames of the injection molded frame, and the portion of the lead wire 7 between the opposite frames is connected to the injection molded frame through the active material, together forming the busbar structure in the battery cell.

[0117] Specifically, the active material can be a lead oxide paste made by mixing and stirring 75% to 95% lead oxide, 1.40% acid solution, and the remainder pure water. The acid solution is determined according to the type of anion in the electrolyte.

[0118] Specifically, the busbar grid uses an injection-molded frame, such as Figure 5a , Figure 5b and Figures 6-7 As shown, the injection-molded frame for the busbar grid includes a first frame 1 near the casting area, a second frame 2 opposite to and parallel to the first frame 1, a third frame 3 connecting one end of the first frame 1 and one end of the second frame 2, and a fourth frame 4 connecting the other end of the first frame 1 and the other end of the second frame 2, wherein the third frame 3 and the fourth frame 4 are parallel.

[0119] The first frame 1 and the second frame 2 are provided with an equal number of corresponding lead wire holes 5; the lead wire holes 5 on the first frame 1 are arranged in a single layer; the lead wire holes 5 on the second frame 2 are arranged in at least two layers, and the lead wire holes between adjacent layers are staggered.

[0120] The term "one-to-one correspondence" means that the projections of the lead wire holes of the first frame 1 and the lead wire holes of the second frame 2 on the electrode plate plane correspond one-to-one.

[0121] Compared with the prior art, in the injection-molded frame for the busbar grid of the present invention, the lead wire holes on the first frame are arranged in a single layer, and the lead wire holes on the second frame are arranged in at least two layers. This allows the lead wires to be distributed in at least two layers within the frame, forming a three-dimensional grid. The multi-layered distribution of lead wires is beneficial for the current transmission during battery use, efficiently applying the current to the active material area, and ensuring uniform distribution of current density in different parts of the plate during charging and discharging. The injection-molded frame for the busbar grid of the present invention allows the lead wires in a single grid to be distributed in multiple layers, equivalent to the multi-layer stacking of a traditional single-layer lead wire grid, but with very little weight change. Moreover, during injection molding, the injection molding compound can achieve reverse coating of the lead wires, allowing for the coverage of the entire grid with a smaller amount of overcoating when coating the active material.

[0122] For example, on the second frame 2, the vertical distance between the centers of two adjacent layers of lead wire holes is less than the diameter of the lead wire hole 5, that is, the two adjacent layers of lead wire holes overlap in the direction of the vertical electrode plane.

[0123] For example, the height h of the overlapping portion of two adjacent wire mesh layers in the direction perpendicular to the second frame is greater than or equal to 1 / 3 of the wire mesh diameter. In this preferred embodiment, the utilization of active material between adjacent wire mesh layers can be promoted, thereby improving the overall utilization rate of active material.

[0124] For example, the height h of the overlapping portion of two adjacent wire holes in the direction perpendicular to the second frame is greater than or equal to 1 / 3 of the wire hole diameter and less than or equal to 2 / 3 of the wire hole diameter.

[0125] For example, the distance between the wire hole near the edge of the second frame and the edge of the second frame is 0.5 mm.

[0126] For example, the thickness of the first frame 1 gradually decreases along the outward extension direction, forming a trapezoidal cross-section. This effectively protects the uncoated composite lead wire from corrosion during its cycle life. Furthermore, the four frames form the square frame of the electrode plate, which can suppress the expansion and shedding of the active material during the cycle life.

[0127] In this invention, the casting-welding area refers to the area where the grid and busbar are cast-welded together. The first frame 1 of the trapezoidal cross-section gradually arranges the multi-layer lead wires into a single layer, facilitating subsequent casting-welding, reducing work difficulty, and improving product qualification rate. Moreover, the distance between the first frame 1 of the trapezoidal cross-section and the outer frame lug is equal to the thickness of the cast-welded busbar. The composite effect here is equivalent to the lug of a traditional electrode plate, but the electrical performance is superior to that of a traditional lug.

[0128] Taking the second frame with two layers of wire holes as an example, the wire holes of the first frame 1 extend from the side close to the second frame to the side far away from the second frame, gradually arranging the two layers of wire holes into a single layer of wire holes.

[0129] For example, the height of the trapezoidal section is based on the lead wire reserved for the thickness of the cast-welded busbar. The height of the trapezoidal section ensures that the composite lead wire reserved during the cast-welding of the busbar is embedded in the lead molten metal of the busbar, and no excess composite lead wire is exposed to the acidic environment.

[0130] For example, the injection-molded frame for the busbar grid further includes a plurality of horizontal ribs 6 disposed within a square frame enclosed by the four side borders. The horizontal ribs 6 are parallel to the first side border 1 and are evenly distributed. The horizontal ribs 6 are perpendicular to the composite lead wire, which serves to stabilize the lead wire and also provides lateral strength support for the active material of the overall electrode plate.

[0131] For example, the cross-sections of the second frame 2, the third frame 3, the fourth frame 4, and the horizontal rib 6 are all rhomboid. The rhomboid design of the frame and the horizontal rib 6 takes into account both demolding during the injection molding process and the reduction of the force exerted on the injection frame by the mechanical deformation of the grid and the expansion of the active material during the cycle life. Regarding demolding, the rhomboid angle represents the maximum demolding angle of the injection molded part; on the other hand, the expansion of the active material during the cycle life is unavoidable, and all the forces generated by the expansion act first on the injection frame. The rhomboid structure reduces the degree of deformation of the injection frame caused by the expansion force, thereby increasing the cycle life.

[0132] For example, a pair of opposite corners in the rhomboid structure of the second border 2, the third border 3, the fourth border 4 and the horizontal rib 6 face the two sides of the electrode plate respectively.

[0133] The thickness of the frame can be determined based on the thickness of the electrode plate. For example, the thickness of the first frame 1, the second frame 2, the third frame 3 and the fourth frame 4 is 0.4-0.8 mm less than the thickness of the electrode plate.

[0134] For example, the thickness of the first border 1, the second border 2, the third border 3 and the fourth border 4 are equal and are 0.2-0.5 mm thicker than the thickness of the horizontal rib 6.

[0135] Secondly, the present invention also provides a busbar grid, the busbar grid comprising lead wire 7 and the injection-molded frame for the busbar grid described above.

[0136] Specifically, the lead wire 7 passes through the lead wire holes corresponding to the first frame 1 and the second frame 2 respectively, and the lead wire is perpendicular to the horizontal rib 6 to form a grid in the square frame.

[0137] It should be noted that the end of the lead wire 7 near the casting and welding area extends beyond the outer edge of the first frame 1, and the extended end of the lead wire is connected to the busbar through a bus connector.

[0138] Thirdly, the present invention also provides an electrode plate, the electrode plate comprising the above-mentioned busbar grid and active material.

[0139] Fourthly, the present invention also provides a composite energy storage battery, the composite energy storage battery comprising a positive electrode busbar 10, a negative electrode busbar 11, a plurality of battery cells 12 and a plurality of the aforementioned electrode plates 9;

[0140] The electrode plate 9 and the battery unit 12 are stacked at intervals;

[0141] The battery cell 12 has two sides with opposite polarities;

[0142] Adjacent battery cells 12 with the same electrode polarity are arranged facing each other and connected by electrode plates 9;

[0143] The electrode plate 9 includes a positive electrode plate and a negative electrode plate;

[0144] The end of the positive electrode plate is connected to the positive electrode busbar 10 via the busbar connector 8;

[0145] The end of the negative plate is connected to the negative busbar 11 via the busbar connector 8.

[0146] In this invention, the positive bus 10 and the negative bus 11 are collectively referred to as busbars.

[0147] In existing energy storage battery busbars, on the one hand, the difference between the input and output currents of the busbar and the maximum conductivity of the overall grid are not considered, resulting in significant energy loss; on the other hand, the battery busbar adopts a split molding technology, and each component needs to be formed with lead alloy. In order to increase the connection strength, the existing technology uses a large amount of lead alloy, which has the disadvantages of adjacent connection structure interlocking and expansion in all directions, and does not meet the design requirements of improving battery safety and miniaturization.

[0148] Based on this, such as Figures 10-12 The busbar of the present invention includes a conductive terminal 01, a screw connection 02, and a busbar grid 03.

[0149] The current collection grid includes multiple conductive ribs 032; each conductive rib 032 is connected to multiple current collection connectors 8, and the current is collected in the conductive rib 032 through the current collection connectors 8; the multiple current collection connectors 8 are distributed along the height direction of the conductive ribs, and each current collection connector 8 can independently collect the current of the electrode plate 9.

[0150] Preferably, multiple conductive ribs 032 are arranged in parallel, and each conductive rib 032 can collect current in each area individually.

[0151] Specifically, multiple busbar connectors 8 converge on one side of the conductive rib, connect to the external circuit through one end of the conductive rib, and form a free end at the other end of the conductive rib.

[0152] Preferably, the merging grid 03 further includes a merging area 031;

[0153] One end of the busbar 031 is fixed with a conductive rib 032, and the other end is connected to an external circuit.

[0154] Specifically, such as Figure 16 As shown, the conductive rib 032 is connected to multiple bus connectors 8 from its free end to the end connected to the bus junction area 031. These connectors are named sequentially as the first bus connector 8a, the second bus connector 8b, ..., the Nth bus connector.

[0155] The current collector 8 collects current and converges it on the conductive rib 032, causing the current flowing from the free end of the conductive rib 032 to the end connected to the current collection area to gradually increase.

[0156] Preferably, the cross-sectional area of ​​the conductive rib 032 gradually increases from the free end to the end connected to the current-collecting area 031, thereby reducing the loss caused by the increase in current.

[0157] Specifically, the cross-sectional area S at each point of the conductive rib 032 satisfies: S≥U×n / (ρ×L0×I0), where U is the electromotive force of the battery cell where the conductive rib 032 is located, L0 is the distance between the first busbar 8a and the second busbar 8b, I0 is the current flowing through the first busbar 8a under the action of U, ρ is the resistivity of the conductive rib 032, and n is the number of busbars connected to the conductive rib 032.

[0158] It should be noted that the number n of the busbar connectors 8 is determined by the processing technology and the electrical loss of the busbar connectors themselves. A larger number of busbar connectors helps to reduce their own losses, but it brings greater processing difficulties (most busbar connectors are made of lead wires extending from the power electrode plate, so their own diameter limits their number and cannot be increased indefinitely). Therefore, n satisfies the following: the interval between adjacent busbar connectors is between 4.8mm and 6.5mm.

[0159] Preferably, the busbar connectors 8 are evenly spaced, and the busbar connectors 8 are evenly distributed on the electrode plates 9, with the interval between adjacent busbar connectors equal to the electrode plate height H2 / (n+1).

[0160] For example, such as Figure 16 As shown, each conductive rib 032 has 14 busbars. On one hand, one end of the busbar 8 is connected to the electrode plate, dividing the electrode plate into 15 regions with uniform height. On the other hand, the other end of the busbar 8 is connected to the conductive rib 032, so that the conductive rib 032 continuously converges from the free end to the end connected to the busbar area 031, collecting the output current from all parts of the electrode plate and transmitting it to the busbar area 031.

[0161] Preferably, the cross-sectional area S at each point of the conductive rib 032 continuously varies to satisfy: S=S0+(Smax-S0)×(L-L0) / (Lmax-L0);

[0162] Where L is the distance from the free end of each part of the conductive rib 032, L0 is the distance between the first busbar 8a and the second busbar 8b, Lmax is the length of the conductive rib 032, S0 is the cross-sectional area of ​​the free end, which can be set according to the design specifications and actual processing conditions; Smax is the cross-sectional area of ​​the end where the conductive rib 032 connects to the busbar area 031, and Smax satisfies: Smax=S0×n.

[0163] It is understandable that (Smax-S0) / (Lmax-L0) is the slope of the change in bus thickness / cross-sectional area.

[0164] It should be noted that an excessively large S0 results in an increase in the width and cross-sectional area of ​​the conductive rib 032, while an excessively small S0 results in greater losses in the conductive rib. S0 should satisfy the following condition: S0 is within 0.5mm. 2 ~10mm 2 between.

[0165] Compared with existing technologies, by Figure 13 As can be seen, this invention gradually increases the cross-sectional area of ​​the conductive ribs from the free end to the end connected to the busbar as the current increases throughout the conductive ribs, forming a slope for the thickness / cross-sectional area change of the busbar. This fully considers the proportional relationship between current density and the cross-sectional area of ​​the conductive busbar, ensuring that the conductive current per square millimeter is the same. This not only controls the relationship between internal resistance and current distribution but also fully utilizes the conductive alloy and active material. Compared with horizontal lead-acid grid batteries, it reduces the increase in losses caused by the increase in incoming current, and at the same time, it reduces the amount of raw materials required compared to conductive ribs of uniform thickness, thus lowering costs.

[0166] Preferably, the height L of each conductive rib connected to the busbar 031 gradually increases from the center of the busbar 031 to both sides.

[0167] It should be noted that the current entering the top of each conductive rib connected in the busbar area is at different distances from the busbar area and the screw connection, and the paths within the busbar area are different, resulting in different actual losses. This can easily lead to uneven output current of each conductive rib, causing different output performance of each conductive rib, busbar connector and the connected battery cell. Over time, this will cause different losses and performance differences of battery cells in different areas, affecting service life and stability.

[0168] Specifically, such as Figure 18 As shown, with the straight line containing the bottom edge of conductive rib 032 as the x-axis, the intersection of the center line of the vertical axis of busbar 1 and the x-axis as the origin, and the height H of conductive rib 032 on its vertical axis center line as the y-axis, a functional relationship between H and X is constructed: H = aX 2 +bX+c, where a=0.0025~0.005, b=-0.5~-1, c=170~180.

[0169] It should be noted that, as Figure 11 As shown, the midpoint P of the line connecting the left and right vertices of the upper part of the conductive rib 032 is defined as the highest point of the conductive rib, and the distance from the highest point of the conductive rib 032 to the bottom edge of the conductive rib 032 is the height H of the center line of the longitudinal axis of the conductive rib; at the same time, the midpoint of the top of the current collection area 031 is defined as O, and the height difference between the top of the current collection area 031 and the highest point of each conductive rib is H1. The line segment PO shows the equivalent current collection path of the conductive rib 032.

[0170] It is understandable that each conductive rib has a corresponding PO line segment representing its equivalent current-carrying path. Each equivalent current-carrying path converges from the center point P at the top of each conductive rib to point O. For clarity and simplicity, Figure 11 The PO line segment only schematically illustrates an equivalent confluence path.

[0171] The inventors discovered that setting the height of the conductive ribs according to the above-mentioned functional relationship between H and X results in lower power loss and output efficiency compared to setting all conductive ribs at the same height, especially when H1 < 15mm.

[0172] Understandably, H1 reflects the height of the busbar 031. A smaller H1 helps to reduce the volume of the busbar 031 and even the busbar itself, thus reducing raw material consumption. However, this also brings the defects of large current loss and uneven current distribution among the conductive ribs.

[0173] Compared with the prior art, the present invention adjusts the height of the conductive ribs according to the position of each conductive rib relative to the current collection area, optimizes the current transmission path of the conductive ribs in the current collection area, reduces losses and makes the output of battery cells in different areas more uniform, which helps to improve the battery's service life and stability.

[0174] The screw connection 02 is a trapezoidal block. The short side of the trapezoidal block is connected to the bottom of the conductive terminal 01, and the long side is connected to the current collection area 031 of the current collection grid 03.

[0175] During implementation, current is collected and transmitted from the busbar 03 to the conductive terminal 01. The long side is connected to the top of the busbar 03, and the bottom side is connected to the conductive terminal 01. The screw connection 02 can bridge the busbar 03 and the conductive terminal 01. The trapezoidal block design can save the amount of screw connection material without increasing the current transmission voltage drop.

[0176] Compared with the prior art, the present invention uses a busbar to combine the current in each region and solves the problem of uneven distribution of output and input current caused by the setting of a single tab (bus connector) in the prior art. Compared with the single tab of the plate of the traditional energy storage battery, the composite energy storage battery of the present invention has dozens or more tabs, and each tab (bus connector) is individually connected to the busbar. This design results in uniform current distribution, high utilization of active material, and strong high current charging and discharging capability.

[0177] It should be noted that during casting and welding, exposed weld lines will be formed in the welding area. These weld lines are slightly higher than the 031 confluence area and trapezoidal block on both sides, forming a protrusion that affects the flatness.

[0178] Preferably, the merging area 031 is fixedly connected to the trapezoidal block by casting and welding, and an external weld line is formed on one side of the bottom surface of the trapezoidal block in the connection area between the trapezoidal block and the merging area 031.

[0179] Compared with the prior art, the present invention forms an external leakage weld line on one side of the bottom surface of the trapezoidal block in the connection area between the trapezoidal block and the busbar area, which can further ensure the flatness of the outer side of the busbar, save battery space, and effectively avoid short circuits caused by the expansion of the weld line leading to the contact of the active material with the conductive electrode post.

[0180] Preferably, such as Figure 14 As shown, the trapezoidal block has a concave arc-shaped connecting part 021 on one side of its short side; the diameter of the arc-shaped connecting part 021 matches the outer diameter of the conductive terminal 01, and the arc-shaped connecting part 021 arc-shapedly covers the outer wall of the conductive terminal 01 in the area where it connects with the conductive terminal 01.

[0181] Preferably, as an example, such as Figures 10-13 As shown, the trapezoidal block is a trapezoidal block with uniform thickness on both the top and bottom surfaces.

[0182] Specifically, the short side of the trapezoidal block is 20mm to 30mm long, the long side is 40mm to 70mm long, and the thickness is 5mm to 20mm.

[0183] Preferably, the top and bottom surfaces of the trapezoidal block are perpendicular to the side of the busbar near the trapezoidal block, and the top and bottom surfaces of the trapezoidal block are perpendicular to the side of the terminal post.

[0184] Preferably, the bottom surface of the conductive terminal 01 is flush with the bottom surface of the trapezoidal block, and the top end face of the busbar 03 is flush with the top surface of the trapezoidal block. This design can make the most of the internal space of the battery case and effectively improve the volumetric energy density.

[0185] Preferably, the screw connection 02 and the conductive terminal 01 are integrally die-cast.

[0186] Specifically, such as Figure 17 As shown, the conductive terminal 01 includes a column 011 and a core 012. The core 012 is nested inside the concave cavity of the column 011. The outer wall of the core 012 and the inner wall of the column 011 are matched and connected to achieve a good conductive path.

[0187] Preferably, the column 011 and the core 012 are integrally formed by die casting.

[0188] Preferably, the core 012 has a screw hole 013 in the central recessed area. The screw hole 013 has threads that can be quickly connected with a matching bolt, which facilitates simple and efficient connection during battery formation or use, and avoids loosening of conductive post connections and increased contact resistance caused by poor contact.

[0189] In the prior art, poor contact can lead to loose connections of conductive posts and increased contact resistance, resulting in increased voltage drop, power loss and insufficient battery charging. Furthermore, due to the increased contact resistance, the temperature of the conductive post can rise sharply when a large current is applied, causing the connection between the conductive post and the screw connection 02 to melt.

[0190] Compared with the prior art, the present invention provides a screw hole in the recessed area of ​​the core, and the screw hole has threads that can be quickly connected with a matching bolt, which facilitates simple and efficient connection during battery formation or use, and avoids loosening of conductive post connection and increased contact resistance caused by poor contact.

[0191] Preferably, the diameter of the core 012 is 10mm to 30mm, and the diameter of the column 011 is 20mm to 40mm.

[0192] Preferably, the height of the column 011 is 30mm to 50mm.

[0193] Preferably, the screw hole 013 has a depth of 15mm to 30mm and a diameter of 5mm to 10mm.

[0194] Preferably, the outer periphery of the column 011 is provided with one or more annular grooves, and the annular grooves are matched with annular O-rings, which can realize the sealed connection between the conductive terminal 01 and the outside.

[0195] Preferably, the width of the annular groove is 2mm to 5mm and the depth is 1mm to 3mm.

[0196] The end of the positive electrode plate in electrode plate 9 is connected to the conductive rib 032 of the positive busbar 10 through the busbar connector 8; the end of the negative electrode plate in electrode plate 9 is connected to the conductive rib 032 of the negative busbar 11 through the busbar connector 8.

[0197] The lead wire for the busbar grid, the injection-molded frame, the busbar grid, the electrode plate, and the composite energy storage battery of the present invention will be further described below through specific embodiments.

[0198] Example 1a

[0199] This embodiment provides a method for forming lead wire, which uses a mold core assembly for producing composite lead wire to prepare composite lead wire with a wire gauge of 1.5mm.

[0200] The composite lead wire forming method includes: introducing molten alloy through alloy inlet 10201, introducing core material (glass fiber) through core material guide mold 10101, the alloy entering alloy conical channel 104, and merging with the core material from core material guide mold 10101 before entering core material coating lead layer channel 10301 for coating, thus forming a composite lead wire. The alloy flow rate in the alloy conical channel 104 is 1.1 times the alloy flow rate in the core material coating lead layer channel 10301; the alloy in the core material coating lead layer channel 10301 generates a thrust of 21 MPa towards the outlet of the core material coating lead layer channel 10301; the alloy temperature is 200℃, and the pressure is 22 MPa.

[0201] The core assembly for producing composite lead wire includes an inlet mold 101, an intermediate mold 102, and an outlet mold 103. The inlet mold 101 and the outlet mold 103 are assembled and connected through the intermediate mold 102. The intermediate mold 102 is provided with an alloy inlet 10201. The diameter of the inlet end of the core material coated lead layer channel 10301 of the outlet mold 103 gradually decreases along the material flow direction, forming a conical inlet end. The end of the core material guide mold core 10101 of the inlet mold 101 is conical, and the cone angle faces the outlet mold 103. The conical end of the core material guide mold core 10101 is located inside the conical inlet end of the outlet mold 103, and an alloy conical channel 104 is formed between the two cones.

[0202] The inlet mold 101 includes an inlet mold base 10102 and a core material inlet mold core 10101, wherein the core material inlet mold core 10101 is provided with a core material inlet channel 10103 for the core material to pass through; the outlet mold 103 includes an outlet mold base 10303 and an outlet mold core 10302, wherein the outlet mold 103 is provided with a core material lead coating layer channel 10301; the intermediate mold 102 is an annular structure, wherein the inlet mold 101 and the outlet mold 103 are respectively assembled at both ends of the intermediate mold 102, specifically, the core material inlet mold core 10101 and the outlet mold core 10302 are respectively assembled in the annular space at both ends of the intermediate mold 102; a cavity is provided between the intermediate mold 102 and the core material inlet mold core 10101, and the core material inlet channel 10103 and the core material lead coating layer channel 10301 are coaxially arranged.

[0203] The angle between the hypotenuse of the tapered end of the core material guide mold 10101 and the horizontal line is 30 degrees; the angle between the hypotenuse of the alloy tapered channel 104 and the horizontal line is 50 degrees. The distance L between the end face of the core material guide mold 10101 and the end of the tapered entrance of the core material lead-coated channel 10301 is half the diameter of the core material lead-coated channel 10301. The projection of the hypotenuse of the tapered end of the core material guide mold 10101 onto the horizontal plane is closer to the entrance end of the entrance mold 101 than the projection of the hypotenuse of the alloy tapered channel 104 onto the horizontal plane.

[0204] The alloy inlet 10201 is directly opposite the inclined side of the tapered end of the core material guide mold core 10101. The intermediate mold 102 is provided with two alloy inlets 10201, and the two alloy inlets 10201 are symmetrical about the axis of the intermediate mold 102.

[0205] The method produces composite lead wires with a breakage frequency of once per day, a diameter deviation of 0.1 mm, a tensile strength of 135 N for 1.5 mm lead wire, and a smooth, burr-free surface.

[0206] Example 1b

[0207] This embodiment provides a lead wire, including a positive lead wire and a negative lead wire, prepared by the method of Example 1a, comprising: a glass fiber core layer and a tin alloy coating layer arranged from the inside out, wherein the glass fiber core layer is a twisted glass fiber rope of 3 strands of glass fiber, and the diameter of the glass fiber rope is 0.8 mm.

[0208] The glass fiber diameter is 0.5mm, and the glass fiber rope twist is 90.

[0209] The weight of glass fiber is 0.110±0.011 g / m.

[0210] The positive electrode lead wire tin alloy coating is a lead-tin alloy with a tin content of 1.2% by mass, and the thickness of the lead-tin alloy coating of the positive electrode lead wire is 0.75 mm.

[0211] The tin alloy coating of the negative electrode lead wire is a lead-tin alloy with a tin content of 0.3% by mass; the thickness of the lead-tin alloy coating of the negative electrode lead wire is 0.6 mm.

[0212] Example 1c

[0213] This embodiment provides a lead wire, including a positive lead wire and a negative lead wire, prepared by the method of Example 1a, comprising: a glass fiber core layer and a tin alloy coating layer arranged from the inside out, wherein the glass fiber core layer is a twisted glass fiber rope of 5 strands of glass fiber with a diameter of 0.4 mm.

[0214] The glass fiber diameter is 0.23 mm, and the glass fiber rope twist is 70.

[0215] The weight of glass fiber is 0.110±0.011 g / m.

[0216] The positive electrode lead wire tin alloy coating is a lead-tin alloy with a tin mass content of 1.3%, and the thickness of the lead-tin alloy coating of the positive electrode lead wire is 0.7 mm.

[0217] The tin alloy coating of the negative electrode lead wire is a lead-tin alloy with a tin content of 0.5% by mass; the thickness of the lead-tin alloy coating of the negative electrode lead wire is 0.6 mm.

[0218] Example 1d

[0219] This embodiment provides an injection-molded frame, a busbar grid, and an electrode plate.

[0220] The injection-molded frame for the busbar grid includes a first frame 1 near the casting and welding area, a second frame 2 opposite to and parallel to the first frame 1, a third frame 3 connecting one end of the first frame 1 and one end of the second frame 2, and a fourth frame 4 connecting the other end of the first frame 1 and the other end of the second frame 2, wherein the third frame 3 and the fourth frame 4 are parallel.

[0221] The first frame 1 and the second frame 2 are provided with an equal number of corresponding lead wire holes 5. The lead wire holes 5 on the first frame 1 are arranged in a single layer. The lead wire holes 5 on the second frame 2 are arranged in two layers, and the lead wire holes in adjacent layers are staggered. On the second frame 2, the height h of the overlapping part of the two adjacent layers of lead wire holes in the direction perpendicular to the electrode plane is 1 / 3 of the diameter of the lead wire hole.

[0222] The thickness of the first frame 1 gradually decreases along the outward extension direction, forming a trapezoidal cross-section. The trapezoidal cross-section of the first frame 1 gradually arranges the two layers of lead wire into a single layer. The height of the trapezoidal cross-section is based on the lead wire reserved for the thickness of the manifold during casting and welding. The height of the trapezoidal cross-section ensures that the composite lead wire reserved during the casting and welding of the manifold is buried in the lead molten metal of the manifold, with no excess composite lead wire exposed to the acidic environment.

[0223] The injection-molded frame for the busbar grid also includes multiple horizontal ribs 6 disposed within a square frame enclosed by four side frames. The horizontal ribs 6 are parallel to the first side frame 1 and are evenly distributed. The cross-sections of the second side frame 2, the third side frame 3, the fourth side frame 4, and the horizontal ribs 6 are all rhomboid. A pair of opposite diagonals in the rhomboid structure of the second side frame 2, the third side frame 3, the fourth side frame 4, and the horizontal ribs 6 respectively face two sides of the electrode plate.

[0224] The thickness of the first frame 1, the second frame 2, the third frame 3 and the fourth frame 4 is 0.5 mm less than the thickness of the electrode plate and 0.5 mm greater than the thickness of the transverse rib 6.

[0225] The busbar grid includes lead wires 7 and the aforementioned injection-molded frame for the busbar grid. The lead wires 7 pass through corresponding lead wire holes in the first frame 1 and the second frame 2, and are perpendicular to the horizontal ribs 6, forming a grid within the frame; one end of the lead wire 7 near the casting / welding area extends beyond the outer edge of the first frame 1. The lead wires are composite lead wires.

[0226] Lead wire 7 is the composite lead wire prepared in Example 1b.

[0227] The electrode plate includes the aforementioned busbar grid and active material.

[0228] Example 2

[0229] This embodiment provides a composite energy storage battery, which includes a positive electrode busbar, a negative electrode busbar, multiple battery cells, and multiple plates of Embodiment 1d;

[0230] The electrode plates and battery cells are stacked alternately.

[0231] The battery cell has two sides with opposite polarities;

[0232] Adjacent battery cells with the same electrode polarity are arranged facing each other and connected by electrode plates;

[0233] The electrode plates include a positive electrode plate and a negative electrode plate;

[0234] The end of the positive electrode plate is connected to the positive electrode busbar via a connector;

[0235] The end of the negative plate is connected to the negative busbar via a connector.

[0236] The composite energy storage battery has 19 positive plates and 20 negative plates, with a plate spacing of 0.2 mm and a plate height H2 of 117 mm. The required busbars are designed according to the requirements of the composite energy storage battery.

[0237] S1: Based on the number of grids, the number of conductive ribs in the positive busbar 1a is determined to be 19, the number of conductive ribs in the negative busbar 1b is 20, and the distance between the conductive ribs of the two busbars is 0.2mm;

[0238] S2: Based on the functional relationship between H and X: H = aX 2 +bX+c, where a=0.005, b=-1, c=180, determine the height H of the longitudinal centerline of each conductive rib in the busbar;

[0239] S3: Select a lead wire with a diameter of 2.0 mm as the busbar for connecting the electrode plate and the conductive rib. Determine the number of busbars to be 14. Select a rectangle with a cross-sectional area of ​​S0 = 7.6 mm × 0.2 mm at the free end. The distance between the first busbar and the second busbar is L0 = H2 / (n+1) = 7.8 mm, and H2 is 117 mm.

[0240] S4: The cross-sectional area of ​​the end where the conductive rib connects to the busbar is Smax = S0 × n = 21.28 mm. 2 The cross-sectional area of ​​the conductive rib is S = S0 + (Smax - S0) × (L - L0) / (Lmax - L0).

[0241] The short side of the trapezoidal block is 20mm long, the long side is 40mm long, and the thickness is 20mm.

[0242] The core has a diameter of 30mm, and the column has a diameter of 40mm.

[0243] The height of the column is 50mm.

[0244] The screw hole has a depth of 30mm and a diameter of 10mm.

[0245] The height difference between the top of the busbar area and the highest point of each conductive rib is H1 = 12 mm, and the design current density of the conductive rib is 3.0 A / mm². 2 .

[0246] The outer circumference of the column is provided with three annular grooves, and the annular grooves are matched with annular O-rings to achieve a sealed connection between the conductive terminal and the outside.

[0247] The annular groove is 4mm wide and 3mm deep.

[0248] Two busbars of the above-mentioned size are selected as the positive and negative busbars of the composite energy storage battery, and the composite energy storage battery is prepared with battery cells and plates, with the plates and battery cells stacked alternately.

[0249] The battery cell has 19 plates with opposite polarities on both sides. The electrodes of adjacent battery cells with the same polarity are arranged facing each other and connected by plates. The battery cell has a design capacity of 633.33Ah, with 19 positive plates and 20 negative plates, each plate providing a capacity of 33.333Ah.

[0250] The end of the positive electrode plate in the electrode plate is connected to the positive electrode busbar through a bus connector and conductive ribs;

[0251] The end of the negative electrode plate in the electrode plate is connected to the negative electrode busbar through a bus connector and conductive ribs.

[0252] The above-mentioned composite energy storage battery was subjected to a 250A charge and 250A discharge test. After 88 cycles, the discharge energy efficiency was 89%; the energy density (10hr) was 95Wh / L; the energy storage cost (battery) was 0.229 yuan / kWh; the total capacity of a single charge was 594.61Ah; the capacity of a single discharge was 579.77Ah; the charge factor was 102.11%; and the utilization rate of active material was 37%.

[0253] Example 3

[0254] This embodiment provides a composite energy storage battery, which includes a positive electrode busbar, a negative electrode busbar, multiple battery cells, and multiple plates from Embodiment 1d.

[0255] The electrode plates and battery cells are stacked alternately.

[0256] The battery cell has two sides with opposite polarities;

[0257] Adjacent battery cells with the same electrode polarity are arranged facing each other and connected by electrode plates;

[0258] The electrode plates include a positive electrode plate and a negative electrode plate;

[0259] The end of the positive electrode plate is connected to the positive electrode busbar via a connector;

[0260] The end of the negative plate is connected to the negative busbar via a connector.

[0261] The composite energy storage battery has 15 positive plates and 16 negative plates, with a plate spacing of 0.2 mm and a plate height H2 of 117 mm. The required busbars are designed according to the requirements of the composite energy storage battery.

[0262] S1: Based on the number of grids, the number of conductive ribs in the positive busbar is determined to be 15, the number of conductive ribs in the negative busbar is 16, and the distance between the conductive ribs of the two busbars is 0.2mm;

[0263] S2: As Figure 18 As shown, according to the functional relationship between H and X: H = aX 2 +bX+c, where a=0.0025, b=-0.5272, c=175.71, determine the height H of the longitudinal centerline of each conductive rib in the busbar;

[0264] S3: Select a 2.0mm diameter lead wire as the busbar connecting the electrode plate and the conductive rib. Determine the number of busbars to be 14. Select a rectangle with a cross-sectional area of ​​S0 = 7.6mm × 0.2mm at the free end. The distance between the first and second busbars is L0 = H2 / (n+1) = 7.8mm, and H2 is taken as 117mm; 9

[0265] S4: The cross-sectional area of ​​the end where the conductive rib connects to the busbar is Smax = S0 × n = 21.28 mm. 2 The cross-sectional area of ​​the conductive rib is S = S0 + (Smax - S0) × (L - L0) / (Lmax - L0).

[0266] The short side of the trapezoidal block is 26mm long, the long side is 54mm long, and the thickness is 10mm.

[0267] The core has a diameter of 20mm, and the column has a diameter of 26mm.

[0268] The height of the column is 40mm.

[0269] The screw hole has a depth of 22mm and a diameter of 8mm.

[0270] The height difference between the top of the busbar area and the highest point of each conductive rib is H1 = 11 mm, and the design current density of the conductive rib is 2.5 A / mm². 2 .

[0271] The outer circumference of the column is provided with three annular grooves, and the annular grooves are matched with annular O-rings to achieve a sealed connection between the conductive terminal and the outside.

[0272] The annular groove is 3mm wide and 2mm deep.

[0273] Two busbars of the above-mentioned size are selected as the positive and negative busbars of the composite energy storage battery, and the composite energy storage battery is prepared with battery cells and electrode plates, with the electrode plates and battery cells stacked alternately.

[0274] The battery cell has 15 plates with opposite polarities on both sides. Adjacent battery cells with the same polarity on one side face each other and are connected by electrode plates. The battery cell has a design capacity of 500Ah, with 15 positive plates and 16 negative plates, and each plate provides a capacity of 33.333Ah.

[0275] The end of the positive electrode plate in the electrode plate is connected to the positive electrode busbar through a bus connector and conductive ribs;

[0276] The end of the negative electrode plate in the electrode plate is connected to the negative electrode busbar through a bus connector and conductive ribs.

[0277] The above-mentioned composite energy storage battery was charged at 250A (I2) and discharged at 250A (C0.5) for 88 cycles, as follows: Figure 19a As shown, the total capacity for a single charge is 469.429 Ah; the capacity for a single discharge is 457.715 Ah; the energy density (10hr) is 94.8 Wh / L; the energy storage cost per kilowatt-hour (battery) is 0.231 yuan / kWh; the charging factor is 102.9%; the C0.5 discharge efficiency is 97.5%; and the utilization rate of active materials is 39%.

[0278] Where I2 represents a 500Ah battery being charged at 250A; discharge capacity is represented by C, where C0.5 equals a discharge current of 500Ah × 0.5.

[0279] Example 4

[0280] This embodiment provides a composite energy storage battery, which includes a positive electrode busbar, a negative electrode busbar, multiple battery cells, and multiple plates of Embodiment 1d;

[0281] The electrode plates and battery cells are stacked alternately.

[0282] The battery cell has two sides with opposite polarities;

[0283] Adjacent battery cells with the same electrode polarity are arranged facing each other and connected by electrode plates;

[0284] The electrode plates include a positive electrode plate and a negative electrode plate;

[0285] The end of the positive electrode plate is connected to the positive electrode busbar via a connector;

[0286] The end of the negative plate is connected to the negative busbar via a connector.

[0287] The composite energy storage battery has 11 positive plates and 12 negative plates, with a plate spacing of 0.2 mm and a plate height H2 of 117 mm. The required busbars are designed according to the requirements of the composite energy storage battery.

[0288] S1: Based on the number of grids, the number of conductive ribs in the positive busbar is determined to be 11, the number of conductive ribs in the negative busbar is 12, and the distance between the conductive ribs of the two busbars is 0.2mm;

[0289] S2: Based on the functional relationship between H and X: H = aX 2 Given a = 0.0025, b = -0.6, and c = 170, determine the height H of the longitudinal centerline of each conductive rib in the busbar.

[0290] S3: Select a lead wire with a diameter of 2.0 mm as the busbar for connecting the electrode plate and the conductive rib. Determine the number of busbars to be 14. Select a rectangle with a cross-sectional area of ​​S0 = 7.6 mm × 0.2 mm at the free end. The distance between the first busbar and the second busbar is L0 = H2 / (n+1) = 7.8 mm, and H2 is 117 mm.

[0291] S4: The cross-sectional area of ​​the end where the conductive rib connects to the busbar is Smax = S0 × n = 21.28 mm. 2 The cross-sectional area of ​​the conductive rib is S = S0 + (Smax - S0) × (L - L0) / (Lmax - L0).

[0292] The short side of the trapezoidal block is 20mm long, the long side is 40mm long, and the thickness is 5mm.

[0293] The core has a diameter of 10mm, and the cylinder 011 has a diameter of 20mm.

[0294] The height of the column is 30mm.

[0295] The screw hole has a depth of 15mm and a diameter of 5mm.

[0296] The outer circumference of the column is provided with two annular grooves, and the annular grooves are matched with annular O-rings to achieve a sealed connection between the conductive terminal and the outside.

[0297] The annular groove is 2mm wide and 1mm deep.

[0298] The height difference between the top of the busbar area and the highest point of each conductive rib is H1 = 13.5 mm, and the design current density of the conductive rib is 2.8 A / mm². 2 .

[0299] Two busbars of the above-mentioned size are selected as the positive and negative busbars of the composite energy storage battery, and the composite energy storage battery is prepared with battery cells and plates, with the plates and battery cells stacked alternately.

[0300] The battery cell has 11 plates with two sides of opposite polarity. The electrodes of adjacent battery cells with the same polarity are arranged facing each other and connected by plates. The battery cell has a design capacity of 366Ah, with 11 positive plates and 12 negative plates, each plate providing a capacity of 33.333Ah.

[0301] The end of the positive electrode plate is connected to the positive busbar via a bus connector and conductive ribs;

[0302] The end of the negative electrode plate is connected to the negative busbar via a bus connector and conductive ribs.

[0303] The above-mentioned composite energy storage battery was charged at 250A and discharged at 250A. After 88 cycles, the total capacity of a single charge was 342.513Ah, the capacity of a single discharge was 336.13Ah, the energy density (10hr) was 95.2Wh / L, the energy storage cost per kilowatt-hour (battery) was 0.231 yuan / kWh, the charge factor was 103.1%, the discharge efficiency was greater than 98.21%, and the utilization rate of active material was 38%.

[0304] Example 5

[0305] This embodiment provides a composite energy storage battery similar to that of Embodiment 3, except that the height h of the overlapping portion of the lead wire holes in two adjacent layers in the direction perpendicular to the second frame is 1 / 4 of the diameter of the lead wire hole. The rest is the same as in Embodiment 3.

[0306] The composite energy storage battery was subjected to a 250A charge and 250A discharge test. After 88 system cycles, the total single charge capacity was 433.28Ah, the single discharge capacity was 405.84Ah, the energy density (10hr) was 94Wh / L, the energy storage cost per kilowatt-hour (battery) was 0.23 yuan / kWh, the charge factor was 97.5%, the C0.5 discharge efficiency was 94%, and the active material utilization rate was 36%.

[0307] Comparative Example 1

[0308] This comparative example provides a composite energy storage battery, wherein the height H of the center line of the longitudinal axis of the conductive ribs is equal to aX. 2+bX+c, where a=0.002, b=-0.5272, c=175.71, and the rest is the same as in Example 3.

[0309] Two busbars of the above-mentioned size were selected as the positive and negative busbars of the composite energy storage battery. The composite energy storage battery was prepared according to the same method as in Example 3. The composite energy storage battery was charged at 250A and discharged at 250A. After 88 cycles, the total single charge capacity was 468.318Ah, the single discharge capacity was 437.877Ah, the charge factor was 102.9%, and the C0.5 discharge efficiency was greater than 93.50%.

[0310] Comparative Example 2

[0311] This comparative example provides a composite energy storage battery, wherein the height H of the center line of the longitudinal axis of the conductive ribs is equal to aX. 2 +bX+c, where a=0.0025, b=-0.4, c=175.71, and the rest is the same as in Example 3.

[0312] Two busbars of the above-mentioned size were selected as the positive and negative busbars of the composite energy storage battery. The composite energy storage battery was prepared according to the same method as in Example 3. The composite energy storage battery was charged at 250A and discharged at 250A. After 88 cycles, the total single charge capacity was 469.121Ah, the single discharge capacity was 433.61Ah, the charge factor was 102.9%, and the C0.5 discharge efficiency was greater than 92.43%.

[0313] Comparative Example 3

[0314] This comparative example provides a composite energy storage battery, H = aX 2 +bX+c, where a=0.0025, b=-0.5272, c=190, and the rest is the same as in Example 3.

[0315] Two busbars of the above-mentioned size were selected as the positive and negative busbars of the composite energy storage battery. The composite energy storage battery was prepared according to the same method as in Example 3. The composite energy storage battery was charged at 250A and discharged at 250A. After 88 cycles, the total single charge capacity was 467.882Ah, the single discharge capacity was 427.878Ah, the charge factor was 102.9%, and the C0.5 discharge efficiency was greater than 91.45%.

[0316] Comparative Example 4

[0317] This comparative example provides a composite energy storage battery, where the height of the conductive ribs is taken as the maximum value of the conductive rib height in Example 3, and the rest is the same as in Example 3.

[0318] Two busbars of the above-mentioned size were selected as the positive and negative busbars of the composite energy storage battery. The composite energy storage battery was prepared according to the same method as in Example 3. The composite energy storage battery was charged at 250A and discharged at 250A for 88 cycles. Figure 19b As shown, the total charging capacity is 486.502Ah, with a retention rate of 112% relative to the theoretical design value; the discharge capacity is 448.172Ah, with a retention rate of 110% relative to the theoretical design value; and the discharge efficiency is 91.88%.

[0319] contrast Figure 19a , 19b It can be seen that, compared with Comparative Example 4, the discharge efficiency of Example 3 is significantly higher than that of the conductive ribs and other components in Comparative Example 4 after multiple cycles.

[0320] Comparative Example 5

[0321] This comparative example provides a composite energy storage battery. The height of the conductive ribs is taken as the maximum value of the conductive rib thickness / cross-sectional area in Example 3. Each conductive rib requires nearly twice the amount of lead material (as can be seen from the cubic volume formula). The rest is the same as in Example 3.

[0322] Two busbars of the above-mentioned size were selected as the positive and negative busbars of the composite energy storage battery. The composite energy storage battery was prepared according to the same method as in Example 3. The composite energy storage battery was charged at 250A and discharged at 250A. After 88 cycles, the total single charge capacity was 469.433Ah; the single discharge capacity was 457.0Ah; the charge factor was 101.8%; and the C0.5 discharge efficiency was 97.53%.

[0323] Compared with Example 3, Comparative Example 5 did not show a substantial improvement in discharge efficiency, and each conductive rib required nearly twice the amount of lead material.

[0324] Compared with existing technologies that collect current from each electrode plate through tabs, the current collection grid of this invention has multiple individually working conductive ribs to make the current distribution more uniform. It can collect current over a larger area on the side of each electrode plate, thus significantly improving working efficiency under high power conditions, rather than being limited to the contact area between the tabs and the electrode plates in existing technologies. Therefore, it can reduce electrical losses and improve reliability.

[0325] Comparative Example 6

[0326] This comparative example provides a composite energy storage battery similar to Example 3, except that the composite lead wire in the grid is set as a single layer. The rest is the same as in Example 3.

[0327] The composite energy storage battery was subjected to a 250A charge and 250A discharge test. After 88 system cycles, the total charge capacity was 433.28Ah, the discharge capacity was 405.84Ah, the energy density (10hr) was 93Wh / L, the energy storage cost per kilowatt-hour (battery) was 0.23 yuan / kWh, the charge factor was 97.5%, the C0.5 discharge efficiency was 93%, and the active material utilization rate was 34%.

[0328] Comparative Example 7

[0329] This comparative example provides a lead wire, which differs from Example 1b in that the glass fiber rope has a twist of 150.

[0330] This comparative example provides a composite energy storage battery. The difference from Example 3 is that the lead wire prepared in this comparative example is used. The composite energy storage battery is charged at 250A (I2) and discharged at 250A (C0.5). After 88 cycles, the total single charge capacity is 462.138Ah; the single discharge capacity is 451.221Ah; the energy density (10hr) is 92.8Wh / L; the charge factor is 101.8%; the C0.5 discharge efficiency is 97.63%; and the active material utilization rate is 38.8%.

[0331] Where I2 represents a 500Ah battery being charged at 250A; discharge capacity is represented by C, where C0.5 equals a discharge current of 500Ah × 0.5.

[0332] Comparative Example 8

[0333] This comparative example provides a lead wire, which differs from Example 1b in that the glass fiber rope has a twist of 50.

[0334] This comparative example provides a composite energy storage battery. The difference from Example 3 is that the lead wire prepared in this comparative example is used. The composite energy storage battery is charged at 250A (I2) and discharged at 250A (C0.5). After 88 cycles, the total single charge capacity is 463.318Ah; the single discharge capacity is 452.121Ah; the energy density (10hr) is 93.0Wh / L; the charge factor is 101.4%; the C0.5 discharge efficiency is 97.58%; and the active material utilization rate is 38.7%.

[0335] Where I2 represents a 500Ah battery being charged at 250A; discharge capacity is represented by C, where C0.5 equals a discharge current of 500Ah × 0.5.

[0336] Comparative Example 9

[0337] This comparative example provides a lead wire, which differs from Example 1b in that the glass fiber diameter is 0.2 mm.

[0338] This comparative example provides a composite energy storage battery. The difference from Example 3 is that the lead wire prepared in this comparative example is used. The composite energy storage battery is charged at 250A (I2) and discharged at 250A (C0.5). After 88 cycles, the total single charge capacity is 462.222Ah; the single discharge capacity is 454.154Ah; the energy density (10hr) is 93.1Wh / L; the charge factor is 101.3%; the C0.5 discharge efficiency is 98.25%; and the active material utilization rate is 38.3%.

[0339] Where I2 represents a 500Ah battery being charged at 250A; discharge capacity is represented by C, where C0.5 equals a discharge current of 500Ah × 0.5.

[0340] Comparative Example 10

[0341] This comparative example provides a lead wire, which differs from Example 1b in that the glass fiber rope has a twist of 0 and is prepared by spirally winding a single glass fiber.

[0342] This comparative example provides a composite energy storage battery. The difference from Example 3 is that the lead wire prepared in this comparative example is used. The composite energy storage battery is charged at 250A (I2) and discharged at 250A (C0.5). After 88 cycles, the total single charge capacity is 458.312Ah; the single discharge capacity is 442.212Ah; the energy density (10hr) is 93.1Wh / L; the charging factor is 100.8%; the C0.5 discharge efficiency is 96.487%; and the active material utilization rate is 37.2%.

[0343] Where I2 represents a 500Ah battery being charged at 250A; discharge capacity is represented by C, where C0.5 equals a discharge current of 500Ah × 0.5.

[0344] The tensile strength of the double-layer hot-melt wire in Examples 1b, 1c, and Comparative Examples 7-10 was tested according to the following method:

[0345] 3.3.1 Instruments and equipment used for testing

[0346] Tensile testing machine, ruler (1m long, 1mm accuracy), paper cutter.

[0347] 3.3.2 Detection Method

[0348] 3.3.2.1 First, use a ruler to cut a glass fiber / hot melt wire about 1m long.

[0349] 3.3.2.2 Wrap the glass fiber / hot melt wire around the tensile tester and clamp the glass fiber / hot melt wire.

[0350] 3.3.2.3 Turn on the tensile tester to conduct the test.

[0351] 3.3.2.4 When the glass fiber / hot melt wire is broken, the glass fiber separates from the lead alloy layer. The tensile force at this time is recorded as the tensile strength of the glass fiber / hot melt wire.

[0352] 3.3.3 Sampling Judgment

[0353] Glass fiber: Random sampling by axial number, single sampling for normal inspection according to GB / T2828.1, special inspection level S-2, AQL=1.0.

[0354] Hot melt line: Random sampling based on the number of shafts, single sampling for normal inspection according to GB / T2828.1, special inspection level S-2, AQL=1.0.

[0355] The shear strength of the lead wires in Examples 1b, 1c, and Comparative Examples 7-10 was tested according to the standard or method of GB / T1450.1-1983 Test Method for Interlaminar Shear Strength of Glass Fiber Reinforced Plastics.

[0356] The corrosion resistance of the lead wires in Examples 1b, 1c, and Comparative Examples 7-10 was tested using the following method: The positive electrode lead wires in Examples 1b, 1c, and Comparative Examples 7-10 were used as the anode of an electrolytic cell under a current of 1A. The acidity of the electrolyte in the electrolytic cell was controlled at an equivalent acidity of 5.4 (mol / L). After continuous operation for one month, the mass loss of the positive electrode lead wires was calculated.

[0357] Conductivity tests were performed on the positive electrode lead wires in Examples 1b, 1c, and Comparative Examples 7-10 according to the standard GB / T 3048.2-1994 "Test Methods for Electrical Properties of Wires and Cables - Test for Resistivity of Metallic Conductor Materials". The specific results are shown in Table 1 below:

[0358] Table 1 Performance Tests of Lead Wire

[0359]

[0360] As shown in the table above, the tensile strength and shear strength of Comparative Examples 7-10 decreased significantly compared to Example 1b, and the corrosion resistance loss of the positive electrode lead wire in Comparative Example 9 increased due to the excessively small diameter of the glass fiber.

[0361] The performance tests of the composite energy storage batteries in Comparative Examples 7-10 and Example 3 show that the charge and discharge capacity of Comparative Examples 7-8 is reduced to a certain extent, and that of Comparative Example 10 is significantly reduced compared to Example 3.

[0362] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A lead wire, characterized in that, include: The glass fiber core layer and tin alloy coating layer are arranged from the inside out. The glass fiber core layer is a glass fiber rope made of multiple strands of glass fiber twisted together.

2. The lead wire according to claim 1, characterized in that, The twist of the glass fiber rope is 70 twists / m to 120 twists / m.

3. The lead wire according to claim 2, characterized in that, The twist of the glass fiber rope is 90±9 twists / m.

4. A lead wire according to claim 3, characterized in that, The glass fiber rope has 3-5 strands of glass fiber and a diameter of 0.2mm-0.8mm.

5. A lead wire according to claim 1, characterized in that, The glass fiber has a diameter of 0.23mm-0.8mm.

6. A lead wire according to claim 1, characterized in that, The tin alloy coating is a lead-tin alloy with a tin mass content of 0.3%-1.3%.

7. A lead wire according to claim 5, characterized in that, The tin alloy coating of the lead wire for the positive electrode is a lead-tin alloy with a tin mass content of 1.0%-1.3%.

8. A busbar grid, characterized in that, Includes the lead wire as described in any one of claims 1-7.

9. An electrode plate, characterized in that, Includes the busbar grid as described in claim 8.

10. A composite energy storage battery, characterized in that, It includes a positive electrode busbar, a negative electrode busbar, multiple battery cells, and multiple electrode plates as described in claim 9; The electrode plates and battery cells are stacked at intervals; The battery cell has two sides with opposite polarities; Adjacent battery cells with the same electrode polarity are arranged facing each other and connected by electrode plates; The electrode plates include a positive electrode plate and a negative electrode plate; The end of the positive electrode plate is connected to the positive electrode busbar via a connector; The end of the negative electrode plate is connected to the negative electrode busbar via a busbar connector; The positive and negative busbars include conductive terminals, screw connections, and busbar grids; The current-collecting grid includes multiple conductive ribs; each conductive rib is connected to multiple current-collecting connectors, and the current is collected in the conductive ribs through the current-collecting connectors. Multiple busbars are distributed along the height of the conductive ribs, and each busbar can collect current from the electrode plate independently.